Comparison of application of different methods to estimate lifetime cardiovascular risk. (April 2016) - Brotons, Carlos; Calvo-Bonacho, Eva; Moral, Irene; Puig, Mireia; Garcia-Margallo, María T; Cortés-Arcas, María V; Catalina-Romero, Carlos; Quevedo-Aguado, Luis; Ruilope, Luis M
Background: Recent guidelines recommend assessment of lifetime cardiovascular risk on the basis of traditional risk factors in adults who are not at high short-term risk. The aim of this study is to determine the implications of estimating the lifetime cardiovascular risk in individuals in a large occupational cohort in Spain. Design: National cross-sectional study in an occupational cohort with an in-person interview including laboratory tests. Methods: Volunteer workers who were examined between January 2011 and December 2011 were included. A total of 580, 236 workers were eligible during this year and 259, 834 were examined (participation rate of 44.7%). Short-term (10-year) and lifetime cardiovascular risk were estimated using the American College of Cardiology (ACC) and the American Heart Association (AHA) tool and the QRISK2 and QRISK. Results: Sixty-eight per cent were male, mean age was 39 years, with an age range of 16 to 75 years. Total number of individuals included in this study was 258, 676. The percentage of patients at high short-term risk was 6.85% (95% confidence interval (CI) 6.75%–6.95% and 20.83% (95% CI 20.60%–21.07%) with the QRISK2, and the ACC/AHA risk equations, respectively. Of the percentage of patients classified as not at high risk with the different tools 1.61% (95% CI 1.55%–1.66%) were high lifetime risk on QRISK, and 27.41% (95% CI 27.11%–27.70%) on ACC/AHA risk. Conclusions: Application of lifetime cardiovascular risk engages greater numbers of individuals at high risk with substantial differences between the different methods available. These differences can have important clinical implications specifically in the percentage of candidates for lifestyle changes and eventually lipid lowering drugs.